Synthesis of binary nanopatterns on hydrogels for initiating cellular responses - Guasch, Judith; Diemer, Jennifer; Riahinezhad, Hossein; Neubauer, Stefanie; Kessler, Horst; Spatz, Joachim P. (Chemistry of materials, 2016)
We describe the synthesis of binary nanostructures consisting of PEG hydrogels decorated with arrays of AuNPs and TiO2NPs, and their orthogonal functionalization with various peptides. These ligands are able to promote or elude cell adhesion through integrins, a family of transmembrane receptors that connect cells with the extracellular matrix (ECM) or other cells. The different cell adhesion behaviors observed depending on the peptides used, proved the functionality of such binary nanopatterns, which we expect to find applications not only in tissue engineering but also in smart cell culture systems and biosensors.
Gesehen am 26.08.2020